Estimation of dabigatran plasma concentrations in the perioperative setting - Douxfils, Jonathan; Lessire, Sarah; Dincq, Anne-Sophie; Hjemdahl, Paul; Rönquist-Nii, Yuko; Pohanka, Anton; Gourdin, Maximilien; Chatelain, Bernard; Dogné, Jean-Michel; Mullier, François (Thrombosis and Haemostasis, 2015)
The perioperative management of dabigatran is challenging, and recommendations based on activated partial thromboplastin time (aPTT) and thrombin time (TT) are unsatisfactory. Dedicated coagulation tests have limitations at plasma concentrations < 50 ng/ml. Therefore, a more sensitive test, which is available 24/7, is required. It was the aim of this study to investigate the performance of the Hemoclot Thrombin Inhibitors® LOW (HTI LOW) kit, a diluted thrombin time, and the STA® – ECA II (ECA-II) kit, a chromogenic variant of the ecarin clotting time, that were developed to measure low dabigatran concentrations, compared to reference dabigatran analysis by liquid chromatography tandem mass-spectrometry (LC-MS/MS). This study included 33 plasma samples from patients treated with dabigatran etexilate who had plasma concentrations < 200 ng/ml. HTI LOW and ECA-II were performed along with HTI, aPTT (STA®-C. K.Prest® and SynthasIL ®) and TT (STA® – Thrombin). All procedures were performed according to recommendations by the manufacturers. Linear (or curvilinear) correlations and Bland-Altman analyses were calculated. For free dabigatran concentrations < 50 ng/ml, the R2 of linear correlations were 0.69, 0.84 and 0.61, with HTI, HTI LOW and ECA-II, respectively. The R2 for TT, STA®-C. K.Prest® and SynthasIL® were 0.67, 0.42 and 0.15. For HTI, HTI LOW and ECA-II, Bland-Altman analyses revealed mean differences of –6 ng/ml (95 %CI: –25–14 ng/ml), 1 ng/ml (95 %CI: –18–19 ng/ml) and –1 ng/ml (95 %CI: –25–23 ng/ml), demonstrating that tests dedicated to measuring low concentrations are more accurate than HTI. In conclusion, the use of HTI LOW or ECA-II to assess low plasma dabigatran concentrations is supported by our findings.
Keywords: Dabigatran; monitoring; perioperative; guidelines